Laserowa korekcja wady refrakcji a zaburzenia widzenia obuocznego – opis przypadku - Zamojska, Ewa; Loba, Piotr; Archacka, Elżbieta; Broniarczyk-Loba, Anna (Klinika Oczna / Acta Ophthalmologica Polonica, 2010)
Laser refractive surgery is a lively developing branch of ophthalmology. There are a numbers of contraindications for this type of surgery, but many of them are difficult to define, for example binocular vision impairment. Accurate analysis of orthoptic examination before refractive surgery, has forced us to dissuade our patient from refractive surgery, despite the fact that there were no other contraindications. Case study: A 33 years old woman referred for refractive surgery because of bilateral myopia (right eye: -5.25 Dsph -0.75 Dcyl ax. 170; left eye: -5.0 Dsph). There was no strabismus or other binocular vision disorders in her history. Orthoptic examination revealed exophoria, slight hyperphoria and considerable bilateral convergence insufficiency, which would have contributed to future strabismic complications.